TEACHERS’ VOICES: THE IMPACT OF AI TOOLS ON ENGLISH TEACHING PRACTICES IN VOCATIONAL HIGH SCHOOLS - Nabila Annisa’; Syaiful Islam (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The rapid development of Artificial Intelligence (AI) in education has transformed English language teaching practices, particularly in Vocational High Schools where technology-based learning is widely implemented. This study aimed to explore English teachers’ perspectives on AI use, analyze its positive and negative impacts on teaching practices, and identify strategies for integrating AI into classroom instruction. The study employed a qualitative approach using a narrative inquiry method. The population consisted of vocational high school English teachers, while four teachers were selected through purposive sampling based on their teaching experience and use of AI in learning activities. Data were collected through narrative-based semi-structured interviews, non-participant observations, and documentation, and were analyzed using narrative analysis. The findings revealed that teachers viewed AI positively while maintaining a critical stance toward its implementation. AI was utilized to improve material preparation efficiency, facilitate information access, and enhance student engagement. However, AI also created challenges, including student dependency, reduced critical thinking, and difficulties in assessing authentic student performance. Teachers addressed these challenges by combining AI-assisted exploration with direct instruction, clarification, and continuous supervision. In conclusion, AI serves as an effective supporting tool in English language teaching when applied purposefully, while teachers remain the central agents responsible for maintaining instructional quality, ethical use, and learning objectives.